2019
DOI: 10.1038/s41436-018-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Sharing data for future research'engaging participants' views about data governance beyond the original project: a DIRECT Study

Abstract: Biomedical data governance strategies should ensure that data are collected, stored, and used ethically and lawfully. However, research participants' preferences for how data should be governed is least studied. The DIRECT project collected substantial amounts of health and genetic information from patients at risk of, and with Type II Diabetes. We conducted a survey to understand participants' future data governance preferences. Results will inform the post-project data governance strategy. Methods A survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 36 publications
4
39
1
Order By: Relevance
“…Re-use of data for purposes that participants do not agree on 30 Distrust of the government as an oversight body for genetic research data 35 Risks are mitigated 15 90% were supportive to share data with universities postproject 36 Maximising the value of resources 14…”
Section: Advancement Of Innovation 30mentioning
confidence: 99%
See 2 more Smart Citations
“…Re-use of data for purposes that participants do not agree on 30 Distrust of the government as an oversight body for genetic research data 35 Risks are mitigated 15 90% were supportive to share data with universities postproject 36 Maximising the value of resources 14…”
Section: Advancement Of Innovation 30mentioning
confidence: 99%
“…Highly secure database 30 36 56% were supportive to share data with commercial companies postproject 36 Reducing waste in research 30 Stigmatisation or repercussions 15…”
Section: Advancement Of Innovation 30mentioning
confidence: 99%
See 1 more Smart Citation
“…49 40 46 Vayena and Blasimme (2017), p. 504. 47 Merson et al (2015), p. 256; see also study by Shah et al (2018), which established that for unknown reasons European research participants prefer to share data with universities and are least happy to share with commercial companies. 48 Denny et al (2015), p. 297.…”
Section: Data Accessmentioning
confidence: 99%
“…24 Second, much of the existing literature investigates patient and public preferences about data sharing and patient control of data access and use. 25,26,27,28,29,30 This focus on preferences is arguably misdirected. Taylor and Taylor found that people under some circumstances were still willing to accept "non-preferred" data sharing models.…”
Section: Introductionmentioning
confidence: 99%